Duplex Real-Time RT-PCR Assays for the Detection and Typing of Epizootic Haemorrhagic Disease Virus - Viarouge, Cyril (Public Library of Science, 2015)
Epizootic haemorrhagic disease virus (EHDV) may cause severe clinical episodes in some species of deer and sometimes in cattle. Laboratory diagnosis provides a basis for the design and timely implementation of disease control measures. There are seven distinct EHDV serotypes, VP2 coding segment 2 being the target for serotype specificity. This paper reports the development and validation of eight duplex real-time RT-PCR assays to simultaneously amplify the EHDV target (S9 for the pan-EHDV real-time RT-PCR assay and S2 for the serotyping assays) and endogenous control gene Beta-actin. Analytical and diagnostic sensitivity and specificity, inter- and intra-assay variation and efficiency were evaluated for each assay. All were shown to be highly specific and sensitive.